Wastewater treatment, reuse, and disposal‐associated effects on environment and health. (14th August 2020) - Choudri, B. S.; Al‐Awadhi, Talal; Charabi, Yassine; Al‐Nasiri, Noura
Abstract: This paper presents the review of the literature published in the year 2019 related to treatment and reuse of wastewater and effects on the environment and human health. The scientific review on the treatment and reuse of wastewaters is divided into various sections in the paper. The review sections cover wastewater management, reuse, removal of microorganisms, and chemical constituents. Besides, the review also covers research focused on wastewater treatment plants, disposal, and the management of wastewater sludge as well as biosolids in the environment. Practitioner points: This paper highlights the review of scientific literature published in the year 2019. Review provide issues related to health risks associated with human and the general environment on the reuse of wastewater, treatment as well as disposal. The literature review covers selected papers relevant to the topic.